Human Error Analysis to Reduce the Risk of Work Accidents at PT XYZ Using HEART and Fuzzy FMEA Methods - Dhea Lailiya Rahma; Tranggono Tranggono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Human error is a significant contributor to workplace accidents in the manufacturing industry, particularly in the sugar production sector at PT XYZ, where specific challenges such as operator inexperience and equipment mismanagement heighten these risks. This study addresses a critical research gap by analyzing human error factors in the sugar production process using the HEART (Human Error Assessment and Reduction Technique) and Fuzzy FMEA (Failure Modes and Effects Analysis) methodologies. The HEART method quantitatively identifies human error probabilities at various production stages, while Fuzzy FMEA evaluates risk levels and prioritizes accident mitigation strategies. Key high-risk activities identified include improper use of the core sampler (HEP: 0.038, Fuzzy RPN: 500), data entry errors (HEP: 0.234, Fuzzy RPN: 120), and misoperation of the centrifugal machine (HEP: 0.304). The lowest risk was associated with slipping due to juice spills (Fuzzy RPN: 332). This innovative integration of HEART and Fuzzy FMEA offers a novel approach to developing effective mitigation strategies, including enhanced operator training, the establishment of standard hygienic sampling procedures, safety morning talks to raise awareness of safety, software training for operators, health checks before starting work, regular review and approval of data, weekly data audits, and the implementation of warning letters for frequent mistakes. By improving these safety systems, this research aims to significantly reduce accident risks and increase operational efficiency in the sugar industry.